Temperature behavior visualization on rubber material involving phase change simulation - Darwis, Roziha; Alias, Norma; Yaacob, Nazeeruddin; Othman, Mohamed Zahry; Abdullah, Nurashikin; Teh, Yuan Ying (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2009)
Material engineers are excited with the design of a new rubber product through the development of a new composite of rubber product. Our research contributes in developing the mathematical simulation based on Gauss-Seidel Red-Black and Gauss-Seidel method to solve the temperature behavior of the rubber elasticity, strength, entropy and classical experiments through reference publications and stimulating rubber physics research elsewhere. The temperature behavior leads to the partial differential equation of heat transfer problem involving phase change simulation. The prototype of the algorithm implement on Linux operating system using C language.Roziha Darwis, Norma Alias, Nazeeruddin Yaacob, Mohamed Othman, Nurashikin Abdullah, Teh Yuan Ying